Socialist governmentality: political formation, revolutionary instruction, and socialist emulation in the CDR, Cuba, 1961-1965 (Revista Tempo e Argumento, 2020)
During the 1960s, the Committees for the Defense of the Revolution (Comités de Defensa de la Revolución [CDR]) took relevant actions along with the Cuban masses, organizing cultural, social, and economic activities that shaped socialism from below. Thereby, through their work, the CDR gave meaning to their own idea of Cuban socialism. In the context of revolutionary upheaval, they were major players in the process of governmentality deployed by the revolutionary project. They willingly participated in their own governance. As a result, the CDR deployed a productive power that actually aimed at improving the lives of fellow Cubans. This article highlights the political formation of CDR members through revolutionary instruction and ideological formation. Also, this is an analysis of the role of CDR members in the revolutionary process beyond political surveillance, focusing on their impact in the everyday lives of Cuban people. The work of the CDR was key to build a new hegemonic project in revolutionary Cuba. They took a significant ideological role, creating and promoting a new cultural hegemony that sought to convince fellow Cubans about the potential benefits that the revolution could eventually bring. Thus, through the work of the CDR, we may see the Cuban Revolution beyond the vanguard.Keywords: Governmentality. Ideology. Socialist Emulation. Representations. Political Formation.